2017
DOI: 10.3904/kjim.2016.302
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypoxia on the acquisition of epithelial-mesenchymal transition and cancer stemness: a possible link to epigenetic regulation

Abstract: A hypoxic microenvironment leads to cancer progression and increases the metastatic potential of cancer cells within tumors via epithelial-mesenchymal transition (EMT) and cancer stemness acquisition. The hypoxic response pathway can occur under oxygen tensions of < 40 mmHg through hypoxia-inducible factors (HIFs), which are considered key mediators in the adaptation to hypoxia. Previous studies have shown that cellular responses to hypoxia are required for EMT and cancer stemness maintenance through HIF-1α an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 79 publications
3
69
0
4
Order By: Relevance
“…A recent study documented that hypoxiainducible factor 1 can enhance P4HA2 expression to subsequently promote collagen fibre alignment [8]. Tumor hypoxia could promote invasion and metastasis by inducing EMT process in various cancers [29][30][31]. We also observed a significant correlation between P4HA2 and HIF1a expression in our study and speculated that hypoxia might regulate the EMT process by enhancing the expression of P4HA2 [32,33].…”
Section: Discussionsupporting
confidence: 76%
“…A recent study documented that hypoxiainducible factor 1 can enhance P4HA2 expression to subsequently promote collagen fibre alignment [8]. Tumor hypoxia could promote invasion and metastasis by inducing EMT process in various cancers [29][30][31]. We also observed a significant correlation between P4HA2 and HIF1a expression in our study and speculated that hypoxia might regulate the EMT process by enhancing the expression of P4HA2 [32,33].…”
Section: Discussionsupporting
confidence: 76%
“…The inactivation of tumor suppressor genes caused by abnormal hypermethylation is particularly important [21]. Studies have shown that hypoxia is one of the important driving forces for DNA methylation imbalance in tumor cells, and interacts with epigenetic regulation mechanisms to promote tumor development [22,23]. In the present study, a total of 12176 DMGs were identified by comparing DNA methylation status in HS-high and HS-low groups.…”
Section: Discussionmentioning
confidence: 84%
“…TGF-β signaling regulates ovarian CSCs through the modulation of tissue transglutaminase 2 (TGM2), which promotes EMT, metastasis and stem celllike phenotype (164,165). Hypoxia, through the expression of HIF-1α and HIF-2α, regulates CSC-associated genes and induces EMT via the TGF-β signaling pathway, which in turn contributes to stemness (166). Cancer cells with an intermediate EMT phenotype display stem cell-like properties accompanied by enhanced resistance to several anti-cancer drugs [ Figure 5; (124)].…”
Section: Epithelial-to-mesenchymal Transition and Stemnessmentioning
confidence: 99%